Profiling online consumers according to their experiences with a special focus on social dimension - DİRSEHAN, TAŞKIN (ELSEVIER SCIENCE BV, 2011)
Strategic marketing management is basically based on segmentation, targeting and positioning. To develop marketing strategies, professionals and academicians increasingly consider customer experiences in recent years. This paper is focused on the segmentation part of marketing strategies combining it with customer experiences. The main objective of this paper is to introduce social experiences beside other experiences to consumer segmentation according to their experiential appeals in order to reveal new consumer profiles. In this way, marketing strategies can be developed on new consumer segments, since previous studies have not considered sensory, affective, creative cognitive, physical and social experiences all together for segmentation. For this purpose, online environment is used because of its expanding social-aimed use. A descriptive research is conducted with 320 participants in Istanbul. The research findings on online brands indicate new customer segments in addition to the existing ones. These segments are named as individual hedonists, highly socials, holistic consumers, action-oriented consumers, knowledge seekers, sense-directed consumers and social utilitarian consumers. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility 7th International Strategic Management Conference
Keywords: customer experiences; experiential marketing; online brands; internet users; CONSUMPTION